2014
DOI: 10.1021/ja510120e
|View full text |Cite
|
Sign up to set email alerts
|

Borane-Catalyzed Room-Temperature Hydrosilylation of Alkenes/Alkynes on Silicon Nanocrystal Surfaces

Abstract: Room-temperature borane-catalyzed functionalization of hydride-terminated silicon nanocrystals (H-SiNCs) with alkenes/alkynes is reported. This new methodology affords formation of alkyl and alkynyl surface monolayers of varied chain lengths (i.e., C5-C12). The present study also indicates alkynes react more readily with H-SiNC surfaces than equivalent alkenes. Unlike other toxic transition-metal catalysts, borane or related byproducts can be readily removed from the functionalized SiNCs. The new method afford… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
114
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 82 publications
(132 citation statements)
references
References 41 publications
13
114
0
1
Order By: Relevance
“…The optical response of the epitaxial layer was described with a Drude-like free carrier response from which the carrier relaxation time and electrical resistivity could be extracted. Extracted doping levels approached 1.7 × 10 19 atoms/cm 3 Ldiode, showing that the samples annealed at 100 mJ/cm 2 exhibited very low values of n, which may be attributed to the absence of implant damage. .…”
Section: Monolayer Doping On Gementioning
confidence: 90%
See 4 more Smart Citations
“…The optical response of the epitaxial layer was described with a Drude-like free carrier response from which the carrier relaxation time and electrical resistivity could be extracted. Extracted doping levels approached 1.7 × 10 19 atoms/cm 3 Ldiode, showing that the samples annealed at 100 mJ/cm 2 exhibited very low values of n, which may be attributed to the absence of implant damage. .…”
Section: Monolayer Doping On Gementioning
confidence: 90%
“…All samples were annealed at 580 °C. Active carrier concentrations approached 2 × 10 19 atoms/cm 3 . The study showed that SOD of Ge is not straightforward, and there are numerous practical process issues still to be resolved.…”
Section: Spin-on Doping In Gementioning
confidence: 94%
See 3 more Smart Citations